Will the Eastern Partnership Become a Driver for Agriculture? - Oksana Okhrimenko; Alexander Okhrimenko (CES Working Papers, 2017)
This article is devoted to the impact of the Eastern Partnership on agricultural production of the member states. ENPARD basic parameters are examined. The results of agricultural development of the states participating in ENPARD and states preparing to join the project was monitored. The Eastern partnership is based on a deep and comprehensive free trade area (DCFTA), economic integration and convergence with EU policies, energy security, human contacts etc. The absolute and relative indicators of agricultural development of the Eastern Partnership countries are analysed. The general and individual problems of the countries are studied. The analysis showed an unequal economic potential for agricultural development. It was noted that the strategic partnership involves interstate cooperation to achieve mutually beneficial internal and external goals.
Keywords: O19; O43; Q17; Q18; 330; Partnership; convergence; agricultural development; economic integration